ANALISIS SEMANTIK PADA SESONGGAN BAHASA BALI DAN KAITANNYA DENGAN ASPEK AKSIOLOGI - Silvia Sari, Gusti Ayu Putu Agung; Wijaya, William (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
Language is a form of communication media to convey information or messages and one of the methods is through proverbs. Proverb is an indirect language which it does not convey the meaning directly but rather use comparison. Proverbs are used as a mean to convey moral value to humans in a form of indirect language or imagery, thus making the meaning of proverbs can be dug deeper. Proverbs in Bahasa Bali is called sesonggan. The aim of this research is to analyze the semantics meaning in sesonggan Bahasa Bali and the connection with axiology. This research uses qualitative method and is supported by documentation method and note-taking technique in collecting the data. The data source is “Modul Pralambang Palajahan Basa Daerah Bali”. The data is analyzed using Semantics theory by Saussure. The data is presented formally and informally using tables with descriptive commentaries. The result of this study is in sesonggan there found signifier, signified and the whole of signified of sesonggan and its ties with axiology.